FROM PERCEPTION TO PERFORMANCE: INVESTIGATING STUDENTS’ LEARNING OUTCOMES IN MOBILE-BASED ENGLISH PROFICIENCY TESTING - Ulinuha, Atik; Parnawati, Tantry Ajeng; Chotimah, Chusnul (Universitas Tribhuwana Tunggadewi, 2025)
This research aims to determine the extent to which students’ English proficiency levels improve over the course of the program as measured by the British Council EnglishScore (BCES), and to evaluate the effect size of the observed change in test scores. The study employed a pre-experimental, one-group pretest-posttest design. English proficiency score was assessed through pre- and post-tests using the BCES platform. The pretest and posttest scores were analyzed using descriptive and inferential statistics. A paired samples t-test was conducted to determine statistical significance, and Cohen's d was calculated to assess the effect size of the intervention. The findings demonstrate a statistically significant improvement in students’ EnglishScore performance following the intervention. However, the effect size indicates that the gain was modest. While students showed progress on average, the improvement was not dramatic, suggesting that the impact of the short-term intervention was limited. These results highlight the importance of sustained instructional design and the need for realistic expectations when implementing short-term English language programs. Future research should consider longer-term interventions, incorporate control groups for comparison, and include qualitative data to better understand learners' experiences and engagement with digital proficiency assessments.